Effectiveness of “Istami” app in enhancing Arabic listening skills: A study at Ats-Tsamina Lil Ummah, Indonesia - Bahrun, Muhammad Farhan; Bakhiet, Bakrie Muhammad; Chamidah, Dewi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The use of instructional media is an urgent necessity, especially with the widespread utilization of educational technology and the increasing number of users. This requires effective integration of such media into the learning process within educational institutions. This aligns with what was stated by Asriyliyya and her colleagues, that ineffective implementation of the teaching and learning process results in low effectiveness, reaching only 48%. However, this issue can be addressed by identifying appropriate instructional media for students. Ats-Tsamina Lil Ummah Institute is one of the institutions striving to utilize instructional media, particularly in its Arabic language course programs. Therefore, this study aims to measure the effectiveness of the